2014
DOI: 10.5812/jjm.13783
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of PER, VEB, SHV, TEM and CTX-M Genes in Resistant Strains of Pseudomonas aeruginosa Producing Extended Spectrum β-Lactamases

Abstract: Background:Pseudomonas aeruginosa is the most common pathogen causing nosocomial infections. Resistance of P. aeruginosa strains to broad-spectrum cephalosporins may be mediated by extended-spectrum β-lactamases (ESBLs).Objectives:We intended to investigate the prevalence of ESBLs and antimicrobial susceptibilities of P. aeruginosa isolated from patients in Zahedan, Iran.Materials and Methods:In this cross-sectional study, during 2012–2013, 116 P. aeruginosa isolates were collected from a teaching hospital in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 14 publications
1
23
3
Order By: Relevance
“…This result was similar to those observed by Toupkanlou, et al, [34] who reported the prevalence rate is 36%. In contrast to our study, a study by Ghaima and Abdulhassan [35] detection the prevalence of ESBL-SHV gene in P. aeruginosa was 52.3%, Bahmani and Ramazanzadeh [36] detected that the prevalence of ESBL-SHV gene in P. aeruginosa was 10.57% and in a study by Bokaeian et al, [37] blaSHV was 6.6%, and Chika and Agbakoba [38] was 43.5%.…”
Section: Discussioncontrasting
confidence: 99%
“…This result was similar to those observed by Toupkanlou, et al, [34] who reported the prevalence rate is 36%. In contrast to our study, a study by Ghaima and Abdulhassan [35] detection the prevalence of ESBL-SHV gene in P. aeruginosa was 52.3%, Bahmani and Ramazanzadeh [36] detected that the prevalence of ESBL-SHV gene in P. aeruginosa was 10.57% and in a study by Bokaeian et al, [37] blaSHV was 6.6%, and Chika and Agbakoba [38] was 43.5%.…”
Section: Discussioncontrasting
confidence: 99%
“…We designed primers for the selected genes found to be most prevalent among clinical studies as well as our own observation from NGS based study and other reports [12–21]. Multiplex PCR Primer designed against drug resistance gene include Group‐1; (ESBL‐MBL) blaTem, blaOXA, blaCTX‐M‐15, blaVim) Group‐2, (blaGes, blaVeb and DIM and AmpC) Efflux pump genes‐ Group‐3 (MexA,B‐oprM); Group‐4 (MexC,D‐oprJ); Group‐5 (Mex X,Y‐oprN) Group‐6 (oprD, nfxB, MexR) primers were purchased from Eurofins Genomics India Pvt Ltd, Bangalore, India.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, 80% of the XDR strains were isolated from tracheal specimens, 5/ Enayatzadeh and colleagues found a significant, positive association between presence of the β-lactamase genes, especially the bla TEM-1 and bla SHV-1 and resistance to β-lactam antibiotics, which signifies the need for new treatment strategies. methods such as PCR have been suggested to be more sensitive (34). Furthermore, we detected significant associations between presence of the βlactamase genes and resistance to β-lactam antibiotics.…”
Section: Discussionmentioning
confidence: 55%